Structure reassignment of two triterpenes with CASE algorithms and DFT chemical shift predictions. Issue 1 (22nd December 2021) - Duan, Zhi-Kang; Lv, Tian-Ming; Song, Guan-Shan; Wang, Yu-Xi; Lin, Bin; Huang, Xiao-Xiao
Abstract: Two triterpenes (14 S, 17 S, 20 S, 24 R )-25-hydroxy-14, 17-cyclo-20, 24-epoxy-malabarican-3-one (CEM, 1a) and (14 S, 17 S, 20 S, 24 R )-20, 24, 25-trihydroxy-14, 17-cyclomalabarican-3-one (CM, 2a ) with a cyclobutane ring were reported, which have the same NMR data as ocotillone (1b ) and gardaubryone C (2b ), respectively. An incorrect structure might be reported. Therefore, the structure reanalysis of these triterpenes was achieved by CASE algorithm and DFT chemical shift predictions, and the results showed that the structures of CEM and CM might be incorrect. To further verify the structure of compound 1, the HMBC, 1 H- 1 H COSY and HSQC-TOCSY spectra were employed. Herein, we revised the structure of CEM and CM, and our study also showed that CASE algorithm and DFT chemical shift predictions can hold the post of effective structure reassignment method. Abstract : UF0001